Deciphering the molecular signal from past and alive bacterial communities in aquatic sedimentary archives. (6th October 2021) - Pearman, John K.; Biessy, Laura; Howarth, Jamie D.; Vandergoes, Marcus J.; Rees, Andrew; Wood, Susanna A.
Abstract: Lake sediments accumulate information on biological communities thus acting as natural archives. Traditionally paleolimnology has focussed on fossilized remains of organisms, however, many organisms do not leave fossil evidence, meaning major ecosystem components are missing from environmental reconstructions. Many paleolimnology studies now incorporate molecular methods, including investigating microbial communities using environmental DNA (eDNA), but there is uncertainty about the contribution of living organisms to molecular inventories. In the present study, we obtained DNA and RNA inventories from sediment spanning 700 years to investigate the contribution of past and active communities to the molecular signal from sedimentary archives. Additionally, a droplet digital PCR (ddPCR) targeting the 16S ribosomal RNA (16S rRNA) gene of the photosynthetic cyanobacterial genera Microcystis was used to explore if RNA signals were from legacy RNA. We posit that the RNA signal is a mixture of legacy RNA, dormant cells, living bacteria and modern‐day trace level contaminants that were introduced during sampling and preferentially amplified. The presence of legacy RNA was confirmed by the detection of Microcystis in sediments aged to ~200 years ago. Recent comparisons between 16S rRNA gene metabarcoding and traditional paleo proxies showed that past changes in bacterial communities can be reconstructed from sedimentary archives. The recovery of RNA in the present study has provided new insights into the origin of these signals. However, caution is required during analysis and interpretation of 16S rRNA gene metabarcoding data especially in recent sediments were there are potentially active bacteria.